2005
DOI: 10.1002/jcp.20469
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule‐dependent nuclear‐cytoplasmic shuttling of Runx2

Abstract: RUNX/AML transcription factors are critical regulators of cell growth and differentiation in multiple lineages and have been linked to human cancers including acute myelogenous leukemia (RUNX1), as well as breast (RUNX2) and gastric cancers (RUNX3). RUNX proteins are targeted to gene regulatory micro-environments within the nucleus via a specific subnuclear targeting signal. However, the dynamics of RUNX distribution and compartmentalization between the cytoplasm and nucleus is minimally understood. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
49
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 49 publications
11
49
3
Order By: Relevance
“…Although Runx2 is localized with mitotic chromosomes, a fraction of Runx2 is extrachromosomal, perhaps in association with microtubules (ref. 34 and our unpublished observations). Our conclusion that Runx2 associates with mitotic chromosomes is based on both microscopic evidence ( Fig.…”
Section: Runx2 Protein Is Stable During Mitosis and Associated With Msupporting
confidence: 64%
“…Although Runx2 is localized with mitotic chromosomes, a fraction of Runx2 is extrachromosomal, perhaps in association with microtubules (ref. 34 and our unpublished observations). Our conclusion that Runx2 associates with mitotic chromosomes is based on both microscopic evidence ( Fig.…”
Section: Runx2 Protein Is Stable During Mitosis and Associated With Msupporting
confidence: 64%
“…18c,d). These results suggest that Runx2 is targeted by NAA10 in the cytoplasm before it enters into the nucleus or while it shuttles between the nucleus and the cytoplasm 23 . To identify the entity responsible for the reversal of the NAA10-mediated acetylation of the RUNT domain, we searched for the deacetylase among HDAC members.…”
Section: Naa10 Negatively Regulates Bone Development In Micementioning
confidence: 79%
“…In contrast, a truncated DCAMKL1 mutant containing mutant, or a control GFP expression vector were transfected into cells expressing myc epitope-tagged Runx2. Analysis of cells transfected with the control GFP expression vector revealed that Runx2 localization was predominantly nuclear sequestration of Runx2 (Pockwinse et al, 2006), we questioned whether DCAMKL1 may repress Runx2 transcriptional activity through sequestering Runx2 in the cytoplasm. To assess this, GFP-tagged DCAMKL1, GFP-tagged DCL WT and Dcamkl1 / mice.…”
Section: Dcamkl1 Regulates the Activity Of Runx2 In Osteoblastsmentioning
confidence: 99%